In order to solve for the variable in the equation 1 minus (x + 2) + 2 x = 5 (2 x minus 5) minus x, Mikel first applies the distributive property. Which equation is a result of this step? 1 minus x + 2 + 2 x = 10 x minus 5 minus x 1 minus x minus 2 + 2 x = 10 x minus 25 minus x 1 minus x minus 1 + 2 x = 10 x minus 25 minus x 1 minus x minus 1 + 2 x = 10 x minus 5 minus x

Respuesta :

Answer:

1-x-2+2x = 10x-25-x

Step-by-step explanation:

The given equation is as follows :

1-(x+2)+2x=5(2x-5)-x

We need to solve the above equation.

Firstly opening bracket off LHS and applying distributive property at RHS.

1-x-2+2x=5(2x)-5(5)-x    (Distributive property :a(b+c) = ab+ac)

1-x-2+2x = 10x-25-x

So, the correct option is (B) i.e. 1 minus x minus 2 + 2 x = 10 x minus 25 minus x.

Answer:

It's b

Step-by-step explanation:

I got it right on edge

ACCESS MORE